2023
DOI: 10.1038/s41598-023-34937-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive identification of combined salinity stress and stalk rot disease caused by Colletotrichum graminicola in maize using Raman spectroscopy

Abstract: Food security is an emerging problem that is faced by our civilization. There are millions of people around the world suffering from various kinds of malnutrition. The number of people that starve will only increase considering the continuous growth of the world’s population. The problem of food security can be addressed by timely detection and identification biotic and abiotic stresses in plants that drastically reduce the crop yield. A growing body of evidence suggests that Raman spectroscopy (RS), an emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Earlier research has shown that biotic stress can induce alterations in polyphenol concentration. For instance, in maize, Colletotrichum graminicola infection leads to an increase in polyphenols, whereas in wheat, Diuraphis noxia infestation results in a decrease ( Higgins et al., 2022 ; Higgins et al., 2023 ). Viral infections have their own pathogenic mechanisms, distinct from the mechanisms utilized by living pathogens, so this difference could potentially explain why the crops did not experience alterations in polyphenol content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier research has shown that biotic stress can induce alterations in polyphenol concentration. For instance, in maize, Colletotrichum graminicola infection leads to an increase in polyphenols, whereas in wheat, Diuraphis noxia infestation results in a decrease ( Higgins et al., 2022 ; Higgins et al., 2023 ). Viral infections have their own pathogenic mechanisms, distinct from the mechanisms utilized by living pathogens, so this difference could potentially explain why the crops did not experience alterations in polyphenol content.…”
Section: Resultsmentioning
confidence: 99%
“…Observed biochemical changes within a crop can then be used to diagnose infection caused by plant pathogens. Previous studies have shown RS’s ability to detect fungal pathogens within wheat, sorghum, and corn using handheld-spectrophotometers ( Egging et al., 2018 ; Higgins et al., 2023 ). Additionally, Mandrile et al.…”
Section: Introductionmentioning
confidence: 99%